Bench scale studies for pretreatment of sanitary landfill leachate with Moringa oleifera seeds extract - Muyibi∗, Suleyman A.; Mohd Noor, Megat Johari; Ahmadun, Fakhrul-Razi; Ameen, Emad (2002)
A laboratory study using a bench scale model of two unit operations involved processes of coagulation (using Moringa oleifera seeds as a natural coagulant) and flocculation-sedimentation have been adopted to treat the leachate from Air Hitam Sanitary Landfill at Puchong in Malaysia. The results of this study has shown, that M. oleifera has a potential for the removal of heavy metals from the leachate, and may be used as a pre-treatment stage for biological treatment to eliminate a portion of the toxic heavy metals, which limit the activity of micro-organisms in the leachate.